Do self-reported pregnancy complications add to risk evaluation in older women with established cardiovascular disease? - Elin Täufer Cederlöf; Nina Johnston; Jerzy Leppert; Pär Hedberg; Bertil Lindahl; Christina Christersson (BMC, 2019)
Abstract Background In postmenopausal women with established cardiovascular disease (CVD), it is unknown whether a history of pregnancy complications are related to multisite artery disease (MSAD), defined as atherosclerotic lesions in at least two major vascular beds. Pregnancy complications are an established risk factor for CVD. This study aimed to investigate the frequency of pregnancy complications and their association to specific atherosclerotic manifestations and prediction of MSAD in older women with and without CVD. Methods In total, 556 women were invited to participate in the study. Of these women 307 reported former pregnancy from a cohort of women with (n = 233) and without CVD (n = 74). The self-reported frequency of pregnancy complications were surveyed retrospectively by a questionnaire that included miscarriage, subfertility, gestational hypertension (GHT) and/or preeclampsia (PE), low birth weight, preterm birth, bleeding in late pregnancy, gestational diabetes mellitus and high birth weight. Three vascular beds were examined, the peripheral, carotid and coronary arteries. Results The mean age was 67.5 (SD 9.5) years. GHT and/or PE tended to be more common, but not significant, in women with CVD than in women without (20.3% vs 10.8%, p = 0.066). Among women with GHT and/or PE, hypertension later in life were more frequent than in women without (66.7% vs 47.4%, p = 0.010). GHT and/or PE were not associated with specific atherosclerotic manifestations or prediction of MSAD. Conclusions In older women with established CVD, pregnancy complications was not associated to specific atherosclerotic manifestations and may not provide additional value to the risk evaluation for MSAD.